Automatic and Controlled Emotion Regulation in Aging: The Case of Expressive Suppression. Issue 2 (15th March 2019) - Zsoldos, Isabella; Fromant, Florine; Hot, Pascal
ABSTRACT: Background/Study Context: To explain the high levels of well-being reported by older adults, socioemotional selectivity theory suggests that emotion regulation becomes more automated with age. Hence, the objective of the present study was to determine whether automatic emotion regulation becomes indeed more efficient with age, as controlled regulation becomes less efficient. We tested this hypothesis with regard to a specific emotion regulation strategy, expressive suppression, and a discrete emotion: disgust. Methods: Disgusting videos were presented to 74 young adults (mean (SD) age: 20.1 (1.8)) and 52 older adults (mean (SD) age: 73.6 (9.3)), randomly assigned to one of three conditions: the control condition, the implicit condition (assessing automatic suppression), and the explicit condition (assessing controlled suppression). The disgust expressed and the disgust felt were analyzed separately with factorial analyses of variance that included age group and regulation condition as between-subject variables. Results: Our results suggest that automatic and controlled expressive suppression may both be altered in healthy aging. Relative to young adults, older adults do not suppress their facial expressions as much but report feeling less disgust. Conclusion: Expressive suppression may not become more automated with age. However, the older adults' ability to suppress facial expressions did not appear to be directly associated with the intensity of their emotions.